Corticospinal Contributions to Neuromuscular Fatigue Following Exausthive Stretch-Shortening Cycle Actions - Bascherini, Jacopo (2024)
Neuromuscular fatigue refers to any exercise-induced decline in force generation capacity. It may stem from disturbances in processes at or distal to the neuromuscular junction, referred to as peripheral fatigue, as well as proximal to it, referred to as central fatigue. Central fatigue can be further distinguished into spinal or supraspinal fatigue. No studies have assessed central fatigue or the degree of supraspinal fatigue after exhaustive stretch-shortening cycle (SSC) exercise. Therefore, the purpose of the present study was to investigate the acute corticospinal contribution to neuromuscular fatigue following exhaustive SSC exercise. Ten healthy active individuals were assigned to the fatigue group (FAT) and completed the SSC fatigue protocol. Ten different individuals did not engage in any exercise, serving as control group (CON). Maximal voluntary contraction (MVC) and tibial nerve electrical, as well as primary motor cortex magnetic stimulation evoked force and surface EMG (M-wave and MEP) responses, were recorded before and immediately after SSC exercise to assess voluntary activation ratio and corticospinal excitability. To assess the magnitude of acute exercise-induced fatigue, assessments of neuromuscular and corticospinal functions were completed within 3.5 minutes after exercise cessation. Ankle plantar flexor MVC for FAT decreased by ~18.12% (p < 0.001; d = 0.89) after exhaustive SSC exercise. Cortical voluntary activation ratio for FAT declined from 90.3 ± 10.1% at baseline to 77.4 ± 15.4% after SSC exercise (p = 0.001, r = 0.79). Voluntary activation ratio measured via motor nerve stimulation declined from 92.7 ± 6.8% at baseline to 82.3 ± 12.9% after SSC exercise (p = 0.037; r = 0.66). Resting twitch amplitude declined by ~ 9.2% (p = 0.03; d = 0.34). Silent period duration lengthened by ~13.5% (p = 0.01; d = 1.38), while MEPs remained unchanged. Thus, exhaustive SSC exercise induced considerable central fatigue and caused an impairment in the capacity of the motor cortex to drive the ankle plantar flexors along with increased level of intracortical inhibition. As a result, maximum force-generation capacity was significantly reduced by central fatigue as well as by peripheral mechanisms following SSC exercise.